A person-centred intervention for providing information to parents of children with cancer. Experiences and effects. Issue 3 (June 2015) - Ringnér, Anders; Karlsson, Stig; Hällgren Graneheim, Ulla
Abstract Purpose The aim of this paper is to describe the experiences of participating in a person-centred information intervention aimed at parents of children with cancer. Methods Eight parents participated in the intervention, beginning two months after their child's diagnosis. The intervention was based upon the representational approach to patient education and a mixed method approach was employed in the study. The experiences of parents and intervention nurses were captured via qualitative interviews and the effects of the intervention on parental psychosocial measures, primarily perceived stress, were evaluated using a single-case design with web-based questionnaires. Results Parents expressed high satisfaction with the intervention, as reported in the follow-up interviews and on the scale measuring satisfaction. However, no changes were seen in the quantitative measures of psychosocial distress. The nurses performing the intervention felt it was useful and feasible. Conclusions A representational approach to providing person-centred information to parents of children with cancer was appreciated and considered feasible by both the parents and the intervention nurses. However, further research is needed considering the lack of effect on the parents' perceived stress.